2019
DOI: 10.1371/journal.pgen.1007423
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal signaling cascades required for phototaxis switch in wandering Leptinotarsa decemlineata larvae

Abstract: Many animals exploit several niches sequentially during their life cycles, a fitness referred to as ontogenetic niche shift (ONS). To successfully accomplish ONS, transition between development stages is often coupled with changes in one or more primitive, instinctive behaviors. Yet, the underlining molecular mechanisms remain elusive. We show here that Leptinotarsa decemlineata larvae finish their ONS at the wandering stage by leaving the plant and pupating in soil. At middle wandering phase, larvae also swit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…After binding of JH, Met recruits another bHLH/PAS protein Taiman (Tai) to form an active receptor complex. The binding of Met/Tai heterodimer to JH response element (JHRE) triggers the transcription of Krüppel-homolog 1 ( Kr-h1 ) and Hairy to repress metamorphosis (Saha et al, 2016; Wu et al, 2016), partially by inhibition of prothoracicotropic hormone (PTTH) signaling (PTTH-Torso-MAPK) to repress 20E biosynthesis and release in Coleopteran for instance the Colorado potato beetle Leptinotarsa decemlineata , the most destructive insect defoliator of potatoes (Meng et al, 2018, 2019), and Lepidopteran such as the tobacco hornworm Manduca sexta (Rountree and Bollenbacher, 1986; Watson and Bollenbacher, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After binding of JH, Met recruits another bHLH/PAS protein Taiman (Tai) to form an active receptor complex. The binding of Met/Tai heterodimer to JH response element (JHRE) triggers the transcription of Krüppel-homolog 1 ( Kr-h1 ) and Hairy to repress metamorphosis (Saha et al, 2016; Wu et al, 2016), partially by inhibition of prothoracicotropic hormone (PTTH) signaling (PTTH-Torso-MAPK) to repress 20E biosynthesis and release in Coleopteran for instance the Colorado potato beetle Leptinotarsa decemlineata , the most destructive insect defoliator of potatoes (Meng et al, 2018, 2019), and Lepidopteran such as the tobacco hornworm Manduca sexta (Rountree and Bollenbacher, 1986; Watson and Bollenbacher, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In L. decemlineata , the main genes that are involved in ecdysteroidogenesis (Wan et al, 2013; Kong et al, 2014), JH biosynthesis (Fu et al, 2016; Li et al, 2016), 20E (Liu et al, 2014; Guo et al, 2015, 2016; Xu et al, 2018a,b, 2019a,c) and JH (Meng et al, 2018, 2019) signaling have been identified. Knockdown of LdMet reduces the body size and accelerates larval development (Meng et al, 2018, 2019), whereas 20E deficient (Kong et al, 2014) or repression of 20E signaling (knockdown of LdEcR, LdUSP, LdHR3, LdHR4, LdE74, LdE75 , or LdFTZ-F1 ) (Liu et al, 2014; Guo et al, 2015; Shi et al, 2016; Xu et al, 2018a,b, 2019a,c) causes failure of larval-pupal-adult ecdysis and lethality. The distinct phenotypes between disturbance of JH and 20E signals will facilitate us to determine the roles of Tai during larval-pupal development.…”
Section: Introductionmentioning
confidence: 99%
“…2). (1) In trained animals the light was switched on in all three arms for 10 s, and the US (electric shocks) was delivered simultaneously. The US consisted of a train of mild electric shocks (2 Hz, 10 V, 200 ms, 20 shocks in total) delivered by the electric grid placed on the floor and ceiling of each arm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, whether light attracts or repels an animal can change during its lifetime, especially if the animal occupies different environments as it ages: some insects switch from positive to negative phototaxis towards the end of their larval stage, as they migrate to a dark refuge (e.g. the soil) to pupate 1,2 . Young nurse bees performing indoor tasks are negatively phototactic, while older foragers are attracted to light 3 .…”
mentioning
confidence: 99%
“…Knockdown of ILP2 in the 3rd instar larvae also significantly reduced the transcript levels of the early JH target gene Krüppel-homolog 1, a zinc finger transcription factor, and a JH biosynthesis gene encoding the Juvenile Hormone Acid Methyltransferase (JHAMT) (Fu et al, 2016). Thus, knockdown of ILP2 delayed the onset of the wandering in L. decemlineata larvae (Meng et al, 2019). Additionally, genes encoding the InR substrate chico and PI 3 K, which meditate insulin signaling, were also down-regulated upon ILP2 silencing (Deng et al, 2018; Figure 3).…”
Section: Insulin-like Peptides (Ilps)mentioning
confidence: 92%